Enhanced solid-state stability of amorphous ibrutinib formulations prepared by hot-melt extrusion - Simões, Marta F. (2020)
One of the applications of Hot-Melt Extrusion (HME) is the stabilization of amorphous drugs through its incorporation into polymeric blends in the form of Amorphous Solid Dispersions (ASDs). In this study, HME was applied to solve a real problem in the development of an ibrutinib product, stabilizing the amorphous form. A systematic approach was followed by combining theoretical calculations, high-throughput screening (HTS) focused on physical stability and Principal Components Analysis (PCA). The HTS enabled the evaluation of 33 formulations for physical stability and the PCA was key to select four promising systems. The low relevance of drug loading on the drug crystallization supported the HME tests with a very high drug load of 50%. Milled extrudates were characterized and demonstrated to be fully amorphous. The thermal analysis detected a glass transition temperature much higher than the predicted values. Along with several weak intermolecular interactions detected in Raman spectroscopy, a dipolar interaction involving the α, β unsaturated ketone function of ibrutinib was also noticed. The additive effect of these intermolecular interactions changed markedly the performance of the ASDs. The physical strength of the prepared systems was corroborated by stability studies until 6 months at long-term and accelerated conditions.